Ebû Talha El-Ensârî Ve Hadis Rivayetindeki Yeri - Demir, Enes (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
Kur’ân-ı Kerîm’in ve Sünnet-i Seniyye’nin nesilden nesile aktarılarak bize kadar ulaşmasında en büyük pay sahâbeye aittir. İslâm Medeniyeti’nin kurucu nesli ve vahyin ilk muhatapları olan sahâbe, hayat içerisinde karşılaştıkları her durumda Allah ve Rasûlü’nün rızasına uygun tavırlar sergilemiş, Kur’ân-ı Kerîm’in takdirine ve Hz. Peygamber’in (s.a.v.) övgüsüne erişmişlerdir. Bu nedenle doğru din anlayışının yeniden tartışmalara açıldığı ve bin dört yüz yıllık İslâm geleneğinin sorgulandığı şu dönemde sahâbeyi tanımak, zihinlerde ve gönüllerde doğru din algısının oluşumuna yardımcı olacaktır.Sahâbî biyografisi ve rivayetleri niteliğinde olan bu çalışmamız, üç bölümden meydana gelmektedir. Çalışmamızın birinci bölümünde, sahâbe neslinin önemli bir kısmını oluşturan “Ensar” hakkında genel bilgiler verilmiş, âyet-i kerîme ve hadîs-i şerifler ışığında ensarın faziletine vurgu yapılmış; ikinci bölümünde, Allah ve Rasûlü’ne sadakati, inananlara karşı sehâveti ve cihad meydanlarında yiğitliği ile tanınan, Enes b. Mâlik’in üvey babası ve Ümmü Süleym’in eşi Ebû Talha el-Ensârî’nin hayatı her yönüyle geniş bir şekilde ele alınmıştır. Çalışmamızın üçüncü bölümünde ise Ebû Talha’nın rivayet ettiği hadisler detaylıca incelenerek hadislerden çıkarılan sonuçlar belirtilmiştir.

The greatest share in the Quran and the words and the deeds of the Prophet (pbuh) being passed down to the next generations and reaching us belongs to the Companions. The founding generation of Islamic civilization and the first addressees of the revelation, the Companions, in every situation they encountered in life, behaved in accordance with the consent of Allah and His Messenger, and attained the discretion of the Quran and the praise of the Prophet (pbuh). For this reason, getting to know the Companions in this period when the correct understanding of religion is opened to the discussion and the Islamic tradition of fourteen hundred years is being questioned will help the formation of the correct religious perception in minds and hearts.This work, which is a Companion biography, consists of three parts. In the first part of our study, general information about ‘Ansar’, which constitutes an important part of the generation of Companions, is given, and the virtue of Ansar is emphasized in the light of verses and hadiths; In the second part, the life of Abu Talha al-Ansari, the stepfather of Anas bin Malik and the husband of Umm Sulaim who is known for his loyalty to Allah and His Messenger, his generosity towards believers, and his valour in jihad squares, has been extensively covered in every aspect. In the third part of our study, the hadiths narrated by Abu Talha were examined in detail and the results obtained from the hadiths were stated.
Abu Talha Al-Ansari and His Position in The Rumor of Hadith
Keywords: Ebû Talha el-Ensârî; Enes b. Mâlik; Ensar; Hadis; Sahâbe; Ümmü Süleym; Abu Talha al-Ansari; Anas bin Malik; Companion; Hadith; Umm Sulaim